Effect of Intrinsic Defects of Carbon Materials on the Sodium Storage Performance. Issue 9 (31st January 2020) - Guo, Ruiqi; Lv, Chunxiao; Xu, Wenjia; Sun, Junwei; Zhu, Yukun; Yang, Xianfeng; Li, Junzhi; Sun, Jin; Zhang, Lixue; Yang, Dongjiang
Abstract: Due to their high conductivity and low cost, carbon materials have attracted great attention in the field of energy storage, especially as anode material for sodium ion batteries. Current research focuses on introducing external defects through heteroatom engineering to improve the sodium storage performance of carbon materials. However, there is still a lack of systematic investigation of the effects of intrinsic defects prevalent in carbon materials on sodium storage performance. Herein, template‐assisted method was used to design carbon materials with different degrees of intrinsic defects and explore their sodium storage properties. The experimental results show that the intrinsic defects in the carbon materials facilitates the adsorption behavior of Na + during the surface induction capacitance process. Among them, the best carbon anode material exhibits high reversible capacity (221 mAh g −1 at 1 A g −1 ) and excellent rate performance. In addition, the density functional theory calculations also show that the existence of intrinsic defects can optimize the distribution of electron density, thereby increasing the Na‐adsorption capacity. This work makes an important contribution to understanding the role of intrinsic defects in the sodium storage performance of carbon materials. Abstract : Carbon materials with porous structure and rich intrinsic defects are synthesized by a simple templates assisted method. The rich intrinsic defects in the microstructure promote the Na + adsorption capacity of carbon materials. This rationally designed carbon‐based material exhibits excellent electrochemical performance in sodium ion batteries.